Bimetallic NiIr nanoparticles supported on lanthanum oxy-carbonate as highly efficient catalysts for hydrogen evolution from hydrazine borane and hydrazine. Issue 9 (16th August 2019) - Hong, Xiaoling; Yao, Qilu; Huang, Meiling; Du, Hongxia; Lu, Zhang-Hui
Abstract : La2 O2 CO3 -supported NiIr nanoparticles (NPs) have been facilely synthesized via a sodium–hydroxide-assisted reduction approach and used as highly efficient catalysts for hydrogen generation from hydrazine borane and hydrous hydrazine. Abstract : Recently, the utilization of hydrazine borane (N2 H4 BH3 ) and hydrous hydrazine (N2 H4 ·H2 O) as promising hydrogen carriers has received increasing research interest. In this work, NiIr alloy nanoparticles (NPs) immobilized on lanthanum oxy-carbonate (NiIr/La2 O2 CO3 ) have been successfully synthesized through a sodium–hydroxide-assisted reduction approach at room temperature. It was found that ultrafine NiIr NPs with an average size of around 2.3 nm were effectively and highly dispersed on La2 O2 CO3 . NiIr/La2 O2 CO3 nanocomposites (NCs) prepared with the assistance of NaOH showed much higher catalytic activity and H2 selectivity toward the N2 H4 BH3 dehydrogenation reaction as compared to those of NiIr/La2 O2 CO3 –N prepared without addition of NaOH. Among all of the tested samples, the optimized Ni0.75 Ir0.25 /La2 O2 CO3 NCs exhibited the highest catalytic performance with 100% hydrogen selectivity for hydrogen generation from an aqueous solution of N2 H4 BH3 . The total turnover frequency (TOF) of Ni0.75 Ir0.25 /La2 O2 CO3 NCs for this dehydrogenation reaction was found to be 1250 h −1 at 323 K, which is among the highest values ever reported. Additionally, this catalyst also exhibited a remarkable catalytic performance for efficient and complete decomposition of N2 H4 ·H2 O. This excellent catalytic performance could be attributed to the high dispersion of metal NPs and the strong interaction between the metal and support as well as the promotion effect of NaOH.